Abscopal Effects of Local Radiotherapy Are Dependent on Tumor Immunogenicity - Lai, Jin-Zhi; Zhu, Yan-Yang; Liu, Ying; Zhou, Lin-Lin; Hu, Li; Chen, Ling; Zhang, Qiu-Yu (Frontiers in Oncology, 2021)
Although abscopal tumor regression remains a rare phenomenon, interest in exploiting how radiation stimulates the immune system to induce systemic abscopal response is increasing. Here, we tested the hypothesis that tumor immunogenicity determined the ability of radiotherapy to induce abscopal effects. We established highly (MC-38 and E.G7-OVA) or poorly (LL/2 and B16-F10) immunogenic tumor models in this study and treated them with sham radiation, a single dose of 15 Gy, or 3 fractions of 5 Gy on three consecutive days. Alterations in the tumor microenvironment after radiation were examined by flow cytometry and RNA sequencing. Our results demonstrated the positive correlation between tumor immunogenicity and the abscopal effect of radiotherapy. The single dose of 15 Gy radiation was an effective regimen for inducing abscopal effects in highly immunogenic tumors. Local radiation reshaped the tumor microenvironment of irradiated and non-irradiated distant tumors by increasing CD8 T-cell infiltration and reducing suppressive immune cell accumulation. However, radiation alone was insufficient to elicit abscopal effects in poorly immunogenic tumors. No significant alterations were detected in the non-irradiated distant tumor microenvironment after radiation of poorly immunogenic tumors. In addition, tumor immunogenic subtypes were associated with the radiological response and clinical outcome of patients receiving radiotherapy. These findings indicated that tumor immunogenicity was the dominant characteristic that could predict the abscopal effect of radiotherapy. Our study provides an in-depth understanding of the immunological mechanisms involved in abscopal effects and highlights the impact of tumor heterogeneity on the therapeutic efficacy of radiotherapy and their combination with immunotherapy in clinical trials.